Hydrogel films of methanolic Mentha piperita extract and silver nanoparticles enhance wound healing in rats with diabetes Type I. Issue 1 (31st December 2022) - Mojally, Mariam; Sharmin, Eram; Alhindi, Yosra; Obaid, Najla A.; Almaimani, Riyad; Althubiti, Mohamed; Idris, Shakir; Abdelghany, Abdelghany H.; Refaat, Bassem; Al-Amodi, Hiba S.; Abdalla, Ashraf N.; Kamel, Hala F. M.
Abstract : Poor wound healing is considered an obstacle in diabetics, which requires effective therapy. Our goal was to investigate the combined effect of mint and silver nanoparticle hydrogel films as wound-healing agents in diabetic rats. Thirty rats were arranged into five groups. The hydrogel films were prepared through an eco-friendly method, excluding toxic solvents and diluents. Gel 1 and fucidin showed complete wound-healing effect on the 22nd day, while Gel 2 showed a faster effect on the 16th day, all compared to group 1 which healed in 25 days. Diabetic rats in group 2 healed beyond 25 days. Moreover, Gel 1 and Gel 2 decreased the fasting blood glucose. Gel 2 enhances wound healing in diabetic rats via multiple mechanisms of action, possibly due to the ability of mint and silver nanoparticles to sustain their concentration at the wound site with limited toxicity. Abbreviations: CO: castor oil; CS: corn starch; DIW: deionized water; H: hydrogel film; H-MME: hydrogel film developed with CS, PVA, CO and MME; H-SMME: hydrogel film developed with CS, PVA, CO and MME/ SNP; MME: methanolic mint extract; PVA: polyvinyl alcohol; SNP: silver nanoparticles; STZ: streptozotocin